The Sublingual Microcirculation Throughout Neonatal and Pediatric Extracorporeal Membrane Oxygenation Treatment: Is It Altered by Systemic Extracorporeal Support? - Erdem, Özge; Kuiper, Jan Willem; van Rosmalen, Joost; Houmes, Robert Jan; Wildschut, Enno D.; Ince, Can; Tibboel, Dick (Frontiers in Pediatrics, 2019)
Background: Extracorporeal membrane oxygenation (ECMO) treatment alleviates systemic cardiorespiratory failure. However, it is unclear whether ECMO also improves microcirculatory function, as the microcirculation can be disturbed despite normal systemic hemodynamics. We therefore aimed to study the sublingual microcirculation (SMC) throughout neonatal and pediatric ECMO treatment. We hypothesized that the SMC improves after starting ECMO, that the SMC differs between venovenous (VV) and venoarterial (VA) ECMO, and that insufficient recovery of microcirculatory disturbances during ECMO predicts mortality. Methods: This single-center prospective longitudinal observational study included 34 consecutive children (April 2016—September 2018). The SMC was assessed daily with a handheld vital microscope (integrated with incident dark field illumination) before, during, and after ECMO. Validated parameters of vessel density, perfusion, and flow quality were assessed for all vessels (diameter <100 μm) and small vessels (<20 μm). Linear mixed models and logistic regression models were built to assess changes over time and identify significant covariates. Using ROC curves, the predictive values of microcirculatory parameters were assessed for mortality on ECMO and overall mortality. Results: The study population comprised 34 patients (median age 0.27 years, 16 neonates, 16 females). Twelve patients were treated with VV and 22 with VA ECMO. Twelve patients died during ECMO (stopped due to futility) and 3 died after ECMO but before discharge. Microcirculatory parameters did not change significantly before, during or after ECMO. Except between microcirculatory flow index (MFI) and mean arterial pressure (MAP), no significant associations were found between microcirculatory parameters and global systemic hemodynamics. The probability of an undisturbed MFI (>2.6) increased with higher MAP (OR: 1.050, 95%CI: 1.008–1.094). Microcirculatory parameters did not significantly differ between VV and VA ECMO or between survivors and non-survivors. None of the microcirculatory parameters could predict mortality on ECMO or overall mortality. Conclusion: In this heterogeneous study population, we were not able to demonstrate an effect of ECMO on the sublingual microcirculation. Microcirculatory parameters did not change throughout ECMO treatment and did not differ between VV and VA ECMO or between survivors and non-survivors. Future research should focus on determining which neonatal and pediatric ECMO patients would benefit from microcirculatory monitoring and how.